Prayer Book Communion and The Spanish Tragedy - Simpson, Lucas (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
This article reads Thomas Kyd’s The Spanish Tragedy within the context of the popular practice of the Prayer Book Communion service contemporary with the play’s performances in Elizabethan playhouses. It stresses the continuities between Kyd’s theatrical appropriation of the Eucharist and a popular conception of the Communion service that emphasizes its role in establishing and affirming public reconciliation, neighbourly concord, and parochial unity. Through an allusion to the Eucharist in Hieronimo’s handkerchief, The Spanish Tragedy deploys the Communion’s penitential, soteriological, and communitarian associations to serve its uniquely theatrical ends. The play’s metatheatrical thematization of representational modalities allows the audience to collectively confront their own sinful desire and then witness their pardon from punishment for that desire at the expense of the onstage representational substitutes.